2015
DOI: 10.5511/plantbiotechnology.15.0205a
|View full text |Cite
|
Sign up to set email alerts
|

Flower color modification in <i>Rosa hybrida</i> by expressing the <i>S</i>-adenosylmethionine: anthocyanin 3′,5′-<i>O</i>-methyltransferase gene from <i>Torenia hybrida</i>

Abstract: We isolated a cDNA encoding S-adenosylmethionine: anthocyanin 3′,5′-O-methyltransferase (A3′5′OMT) from a cDNA library derived from Torenia hybrida petals that mainly accumulated malvidin type anthocyanins using the petunia A3′OMT cDNA as a probe. The torenia A3′5′OMT shared 52-72% amino acid sequence identity with previously reported AOMTs and belongs to the Group A1 methyltransferase family that also include caffeoyl CoA O-methyltransferase. The recombinant A3′5′OMT produced by Escherichia coli efficiently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Km and kcat values for delphinidin 3-O-glucoside of NmAMT6 were 26.8±4.67 µM and 13,100±312 s −1 , respectively. The Km value of NmAMT6 is consistent with that of torenia (Nakamura et al 2015), grape (Hugueney et al 2009), tomato (Roldan et al 2014, and peony (Du et al 2015) for anthocyanins ranging from 1.1-123 µM. This study confirms that flavonoid/anthocyaninrelated genes could be comprehensively isolated by transcriptome analysis of petals.…”
Section: Functional Analysis Of Nmf3h Nmf3′ 5′ H and Nmamtsupporting
confidence: 83%
See 1 more Smart Citation
“…Km and kcat values for delphinidin 3-O-glucoside of NmAMT6 were 26.8±4.67 µM and 13,100±312 s −1 , respectively. The Km value of NmAMT6 is consistent with that of torenia (Nakamura et al 2015), grape (Hugueney et al 2009), tomato (Roldan et al 2014, and peony (Du et al 2015) for anthocyanins ranging from 1.1-123 µM. This study confirms that flavonoid/anthocyaninrelated genes could be comprehensively isolated by transcriptome analysis of petals.…”
Section: Functional Analysis Of Nmf3h Nmf3′ 5′ H and Nmamtsupporting
confidence: 83%
“…Interestingly, the ratio of malvidin glucosides produced varied depending on substrates. The low production of malvidin glucosides by NmAMT6 and petunia MT2 AMT is in contrast to that by grape (Hugueney et al 2009), petunia MF1 and MF2 (Provenzano et al 2014), and torenia (Nakamura et al 2015) AMTs, which were demonstrated to efficiently catalyze 3′ and 5′ methylations of delphinidin glucosides to yield malvidin glucosides. Cyclamen AMT was also shown to catalyze malvidin production (Akita et al 2011).…”
Section: Functional Analysis Of Nmf3h Nmf3′ 5′ H and Nmamtmentioning
confidence: 81%
“…Peonidin‐type anthocyanins are biosynthesized from cyanidin‐based anthocyanins through a methylation reaction catalyzed by the anthocyanin O ‐methyltransferase enzyme. It has been suggested that methylation in plant tissues occurs by producing an alteration in the perceived hue of the pigments, resulting in the reddening/purpling/bluing of flower color . Thus, the presence of considerable amounts of cya 3‐glu and peo 3‐(6 M)‐glu (with their sum accounting for more than 80% of the total anthocyanins in most of the sampled varieties) in pigmented young shoots and flowers in the investigated Citrus genotypes could be explained by the need of Citrus plants to activate biomechanisms targeted at brightening the color of the young tissues to simultaneously assure UV photoprotection and pollinator attraction.…”
Section: Resultsmentioning
confidence: 96%
“…Flavanone 3-hydroxylase (F3H) catalyzes flavanone into flavonol and one to two F3H genes were found to be cloned in most plants, and F3H gene has two introns with 350-380 amino acids in protein (Laura, 2013;Kumar et al, 2015). Flavonoid 3′-hydroxylase (F3'H) and flavonoid 3′5′-hydroxylase (F3'5'H), both of which belong to the cytochrome P450 superfamily, catalyze hydroxylation at the 3′ and 3′, 5′ positions of the B-ring of the flavonoids (Forkmann et al, 2014;Nakamura et al, 2015). Dihydroflavonol 4-reductase (DFR), only expressed in the colored organ responsible for anthocyanidin production, catalyzes flavanonols into leucoanthocyanidin (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%